Metaboreflex and performance in elite female soccer: effects of inspiratory muscle training - Archiza, B.; Andaku, D. K.; Caruso, F. R.; Ricci, P. A.; Bonjorno Jr., J. C.; Oliveira, C. R.; Phillips, S. A.; Arena, R.; Borghisilva, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Inspiratory muscle training (IMT) is an established way to improve strength (S) and endurance (E) of inspiratory muscles. It has been extensively studied and used as an important tool in sports performance, mainly for those aerobic in nature. The objectives of this study are to test the effects on metaboreflex and exercise performance in a professional athlete cohort. Methods: Eighteen professional female soccer players were recruited and underwent a cardiopulmonary exercise test. Subjects were randomized to placebo (PG) and IMT (IMTG) groups. Subsequently, they underwent tests of lung function, S and E of inspiratory muscles, constant high-load exercise testing (CLET) and repeated-shuttle-sprint ability test (RSSA). Near-infrared spectroscopy assessed oxygenation ([oxyHb] and [tHb]) of respiratory (intercostals) and peripheral (vastus lateralis) muscles during CLET and blood samples were taken to analyze lactate concentration ([L]). After 6-weeks of IMT [30 inspiratory efforts, twice/day, 5 days/week, IMTG training at 50% of maximal inspiratory pressure with load adjustments every week], subjects were reevaluated. Results: There were significant improvements observed in the IMTG following IMT: 1) gain of inspiratory muscles S (19.45 ± 10.91 %) and E (53.06 ± 32.51 %); 2) greater exercise tolerance (P<0.05) and reduced [L] over time (P<0.05) in CLET; 3) [oxyHb] of intercostals muscles was higher (from -8.66 ± 4.96 to -1.94 ± 8.50 umol/cm) while [tHb] was also higher in the vastus lateralis (from 2.21 ± 5.60 to 5.56 ± 7.21 umol/cm), and; 4) soccer performance inferred by RSSA was better after IMT (P<0.05). Discussion: Recent evidence shows that IMT could affect lactate recovery, indicating that respiratory muscles are capable of lactate clearance, reducing [H+] and metabolites (Brown et al., 2009). This could explain the increased exercise tolerance and improved athletic performance (Nicks et al. 2009). Likewise, blunted metaboreflex` responses were observed post-IMT only in the IMTG, indicating an increase of [oxyHb] and [tHb] in respiratory and peripheral muscles, respectively, in accordance with previous study (Witt et al., 2007). We conclude that IMT is an important and effective strategy to enhance exercise performance in professional women soccer players.